'A matter of skin': Chantal Akerman's 'porous narratives'. (1st September 2019) - Jacquin, Maud
In 2004, Chantal Akerman created two works – a feature film Tomorrow We Move (Akerman, 2004) and a video installation To Walk Next to One's Shoelaces in an Empty Fridge (Akerman, 2004) – which feature the diary that her Jewish maternal grandmother had kept before dying at Auschwitz. Prompted by the contradictions manifest in the installation (spontaneity vs control; uniqueness vs familiarity), I will argue for an intricate interrelation between the documentary video and the fiction film. In relation to the thematic content of both works, I will subsequently demonstrate that the 'porous' form of narrative that this assemblage generates allows Akerman to challenge and transform dominant conceptions of storytelling, identity, history and memory. In particular, through analysing the modes of writing she portrays in both films in relation to Virginia Woolf 's work, I will contend that Akerman is deeply aware of the political implications of thinking porously.